Simplify x(y + z) + x(w + y) + w(x – z).

1. 2xy + xz + xw + wx – wz
2. 2xy + xz + 2xw – wz
3. xy + xz + xw + xy + wx – wz
4. xw + xy + xy + xz + wx – wz

Respuesta :

a * (b + c) = a * b + a * c

x(y + z) + x(w + y) + w(x - z) = xy + xz + xw + xy + xw - wz = 2xy + xz + 2xw - wz

Answer: 2.

Answer:

[tex]\boxed{\boxed{\tt 2)\: 2xy + xz + 2xw - wz}}[/tex]

Step-by-step explanation:

[tex]\tt x(y + z) + x(w + y) + w(x - z)[/tex]

Expand by distributing terms:

  • [tex]\tt x\left(y+z\right)[/tex] → [tex]\tt xy+xz[/tex]
  • [tex]\tt x\left(w+y\right)[/tex] → [tex]\tt xw+xy[/tex]
  • [tex]\tt w\left(x-z\right)[/tex] → [tex]\tt xw-zw[/tex]

[tex]\tt xy+xz+xw+xy+xw-zw[/tex]

Combine like terms:

[tex]\tt xy+xy+xz+xw+xw-zw[/tex]

[tex]\tt (xy+xy)+xz+(wx+wx)-wz[/tex]

Simplify:

[tex]\tt 2xy+xz+2wx-wz[/tex]

____________________________

ACCESS MORE